Development and validation of the Flare-OA questionnaire for measuring flare in knee and hip osteoarthritis. Issue 5 (May 2022) - Traore, Y.; Epstein, J.; Spitz, E.; March, L.; Maillefert, J.-F.; Rutherford, C.; Ricatte, C.; Alleyrat, C.; Cross, M.; King, L.K.; Callahan, L.F.; Fautrel, B.; et al.
Summary: Objective: Ability to assess flares in osteoarthritis (OA) of the knee and hip (KHOA) is important in clinical care and research. Using mixed methods, we developed a self-reported instrument measuring flare and assessed its psychometric properties. Methods: We constructed questionnaire items from semi-structured interviews and a focus group (patients, clinicians) by using a dual-language (English-French) approach. A Delphi consensus method was used to select the most relevant items. Patients with OA from Australia, France and the United States completed the preliminary Flare-OA, HOOS, KOOS and Mini-OAKHQOL questionnaires online. We used a factor analysis and content approach to reduce items and determine structural validity. We tested the resulting questionnaire (score 0–100) for internal consistency, convergent and known-groups validity. Results: Initially, 180 statements were generated and reduced to 33 items in five domains (response 0 = not at all, to 10 = absolutely) by Delphi consensus (50 patients, 116 professionals) and an expert meeting. After 398 patients (mean [SD] age 64 [8.5] years, 70.4% female, 86.7% knee OA) completed the questionnaire, it was reduced to 19 items by factor analysis and a content approach (RMSEA = 0.06; CFI = 0.96; TLI = 0.94). The Cronbach's alpha was >0.9 for the five domains and the whole questionnaire. Correlation coefficients between Flare-OA and other instrument scores were as predicted, supporting construct validity. The difference in Flare-OA score between patients with and without flare (31.8) largely exceeded 2 SEM (10.2). Conclusion: Flare-OA is a valid and reliable patient-reported instrument for assessing the occurrence and severity of flare in patients with KHOA in clinical research.